Effect of Canagliflozin on Renal and Cardiovascular Outcomes across Different Levels of Albuminuria: Data from the CANVAS Program - Brendon L. Neuen; Toshiaki Ohkuma; Bruce Neal; David R. Matthews; Dick de Zeeuw; Kenneth W. Mahaffey; Greg Fulcher; Qiang Li; Meg Jardine; Richard Oh; Hiddo J.L. Heerspink; Vlado Perkovic (2019)
Significance Statement Albuminuria commonly occurs in people with type 2 diabetes and is an independent risk factor for progression of kidney disease and cardiovascular events. SGLT2 inhibitors are thought to protect the kidneys by lowering albuminuria. If this is true, it suggests people with type 2 diabetes with higher levels of albuminuria would reap greater renoprotective benefits. The authors conducted a post-hoc analysis of data from the CANagliflozin cardioVascular Assessment Study (CANVAS) Program to assess renal, cardiovascular, and safety outcomes with canagliflozin by baseline albuminuria subgroups (urinary albumin/creatinine ratio <30, 30–300, and >300 mg/g). The data suggest that the relative effects of canagliflozin on renal and cardiovascular outcomes are mostly consistent across different levels of baseline albuminuria, but participants with severely increased albuminuria saw the largest absolute benefits. Background If SGLT2 inhibitors protect the kidneys by reducing albuminuria as hypothesized, people with type 2 diabetes mellitus (T2DM) with higher albuminuria should benefit more. Methods We conducted a post-hoc analysis of data from the CANagliflozin cardioVascular Assessment Study (CANVAS) Program, which randomized 10,142 participants with T2DM and high cardiovascular risk to canagliflozin or placebo. We assessed effects of canagliflozin on renal, cardiovascular, and safety outcomes by baseline albuminuria. The trial included 2266 participants (22.3%) with moderately increased albuminuria (urinary albumin/creatinine ratio [UACR] 30–300 mg/g) and 760 (7.5%) with severely increased albuminuria (UACR >300 mg/g) at baseline. Results Canagliflozin lowered albuminuria with greater proportional reductions in those with moderately and severely increased albuminuria ( P heterogeneity<0.001). After week 13, canagliflozin slowed the annual loss of kidney function across albuminuria subgroups, with greater absolute reductions in participants with severely increased albuminuria (placebo-subtracted difference 3.01 ml/min per 1.73 m 2 per year; P heterogeneity<0.001). Heterogeneity for the renal composite outcome of 40% reduction in eGFR, ESKD, or renal-related death was driven by lesser effects in participants with moderately increased albuminuria ( P heterogeneity=0.03), but no effect modification was observed when albuminuria was fitted as a continuous variable ( P heterogeneity=0.94). Cardiovascular and safety outcomes were mostly consistent across albuminuria levels including increased risks for amputation across albuminuria subgroups ( P heterogeneity=0.66). Greater absolute risk reductions in the renal composite outcome were observed in participants with severely increased albuminuria ( P heterogeneity=0.004). Conclusions The proportional effects of canagliflozin on renal and cardiovascular outcomes are mostly consistent across patients with different levels of albuminuria, but absolute benefits are greatest among those with severely increased albuminuria.